Improving the effectiveness and inclusiveness of alcohol and other drug outreach models for young people: a literature review. (4th March 2023) - Fomiatti, Renae; Farrugia, Adrian; Fraser, Suzanne; Hocking, Stephanie
Abstract: While outreach is a common modality for delivering alcohol and other drug support services, little is known about its role for young people experiencing difficulties associated with alcohol and other drug consumption. In this article, we conduct a review of international literature on youth alcohol and other drug outreach to identify features of high-quality outreach models and document major themes or issues. We found relatively little research on youth alcohol and other drug outreach over the last decade, with little critical engagement with the concept and related practices for alcohol and other drug service delivery. Notwithstanding these limitations, our review identified the features the studies found to be best practices or to lead to the most positive outcomes for young people. We conclude with a discussion of future research directions to expand the knowledge base and improve the effectiveness and inclusiveness of alcohol and other drug outreach models for young people.